USE OF MEANS OF MONEY-CREDIT REGULATION OF ECONOMIC PROCESSES: EXPERIENCE OF FOREIGN COUNTRIES WITH MARKET ECONOMY - STEPANENKO, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to analyze the means of monetary regulation of economic processes in foreign countries with market economies. Monetary regulation acts both as an element of stabilizing the economic situation in the country and as one of the components of public policy. For banks, monetary regulation is considered as one of the methods of managing their activities by the central bank. It is determined that the study of improving monetary policy in the context of globalization remains relevant, especially during the implementation of anti-crisis economic policy of the state. The main goals and regulatory functions of individual tools are shown.The use of monetary policy instruments abroad in the aspect of development is analyzed. Development trends, problems of monetary policy regulation are considered. An analysis of the features of medium-term strategy and tactics in the use of instruments of monetary regulation by central banks of the United States and the European Union in the financial crisis have been done. The policy of central banks is fundamental in shaping the financial and credit and banking systems of EU member states and determines the stability of the euro and the main indicators of economic development.The monetary mechanism of economic processes regulation is considered, which includes a set of forms, tools and methods of economic activity intensification, relations and interaction between subjects and objects of regulation of economic processes and provides sustainable economic development. The basic strategies of monetary policy and broad monetary tools of monetary policy are analyzed. The main instruments of monetary policy are outlined: inflation targeting, interest rate policy, open market operations, reserve requirements regulation, and the impact on the national currency exchange rate. It is pointed out that the credit systems of leading foreign countries are quite similar in their structure, they have a number of similar features. It is noted that in accordance with the main priorities of economic policy, an important prerequisite for sustainable economic growth is the intensification of investment activities by economic means, among which the leading role belongs to monetary policy.
Keywords: monetary systems of foreign countries; monetary policy; monetary circulation; instruments; and methods of monetary policy